2020
DOI: 10.1038/s41374-019-0305-y
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 is dispensable for the development of airway allergic asthma

Abstract: Allergic asthma is one of the most common immune-mediated disorders affecting the lungs. It is characterized clinically by airway hyperresponsiveness, eosinophilia, enhanced IL-4 and IL-13, peribronchial inflammation with mononuclear cell infiltration, and goblet cell hyperplasia associated with increased mucus production. However, chronic asthma with repeated exposures to inhaled allergens can result in subepithelial pulmonary fibrosis. The transient receptor potential cation channel subfamily V member 4 (TRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Asthma is a chronic inflammatory disease of the upper airways induced by repeated exposure to specific allergens, which results in activation of epithelial cells and acute bronchoconstriction [77]. In a chicken ovalbumin (OVA) model of asthma, TRPV4-/-mice developed similar levels of airway hyper-responsiveness compared to wild-type (WT) mice [78], although TRPV4 protein levels were increased in WT animals [79]. TRPV4deficient mice were however protected from airway remodeling in a house dust mite (HDM) model, which is more relevant to the human situation [80].…”
Section: Trpv4 Function In the Upper Respiratory Tract And Bronchimentioning
confidence: 99%
“…Asthma is a chronic inflammatory disease of the upper airways induced by repeated exposure to specific allergens, which results in activation of epithelial cells and acute bronchoconstriction [77]. In a chicken ovalbumin (OVA) model of asthma, TRPV4-/-mice developed similar levels of airway hyper-responsiveness compared to wild-type (WT) mice [78], although TRPV4 protein levels were increased in WT animals [79]. TRPV4deficient mice were however protected from airway remodeling in a house dust mite (HDM) model, which is more relevant to the human situation [80].…”
Section: Trpv4 Function In the Upper Respiratory Tract And Bronchimentioning
confidence: 99%
“…Other TRPV channels such as TRPV4 channels may be dispensable for the development of allergic asthma [56]. TRPV4 knockout and wild-type mice sensitized and challenged by OVA express similar levels of allergenspecific IgE, Th2 cytokines, and eosinophils [56].…”
Section: Transient Receptor Potential Vanilloid Channelsmentioning
confidence: 99%
“…Other TRPV channels such as TRPV4 channels may be dispensable for the development of allergic asthma [56]. TRPV4 knockout and wild-type mice sensitized and challenged by OVA express similar levels of allergenspecific IgE, Th2 cytokines, and eosinophils [56]. Although TRPV4 knockout mice have slightly higher AHR in response to increasing doses of β-methacholine than wild-type mice, there are no significant differences in airway resistance between these groups [56].…”
Section: Transient Receptor Potential Vanilloid Channelsmentioning
confidence: 99%
“…arachidonic acid metabolites such as 5,6-epoxyeicosatrienoic acid) stimuli (Garcia-Elias et al 2014). Distribution of TRPV4 in various tissues, such as airway (Palaniyandi et al 2020), heart (Adapala et al 2020), skin (Szabo et al 2019), intestine (Huang et al 2018), brain (Shibasaki et al 2020) and the urinary bladder, has been reported. With significant changes in bladder functions noted in TRPV4 deficient mice (Gevaert et al 2007), there has been a growing interest in TRPV4 as a therapeutic target for bladder dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Distribution of TRPV4 in various tissues, such as airway (Palaniyandi et al . 2020), heart (Adapala et al . 2020), skin (Szabo et al .…”
Section: Introductionmentioning
confidence: 99%